Summer aspect of myxomycete biota in the national nature park “Prypiat’-Stokhid” (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The summer aspect of myxomycete biota in national nature park “Prypiat’-Stokhid” (Western Polissya) has a high species and taxonomic diversity. 39 species of myxomycetes from 17 genera, nine families and five orders Ceratiomyxales, Liceales, Physarales, Stemonitales and Trichiales were recorded in alder, hornbeam, oak, mixed, pine forests and spruce plantations in summer 2010. Ceratiomyxa fruticulosa (O.F.) Müll.) T. Macbr. was noted as the most wide-spread species in all studied forest communities, Arcyria cinerea (Bull.) Pers. was only absent in pine forests and Stemonitis fusca was only absent in spruce plantations. Other 36 species have more limited distribution in park forests. Comparison between the slime molds of park “Prypiat’-Stokhid” and Schatsk national nature park (Western Polissya) shows differences in species and taxonomic diversity in both, summer and autumn aspects .
Keywords: myxomycetes, slime molds, diversity, national nature park “Prypiat’-Stokhid”, Ukraine.